How can teachers encourage students’ agentic engagement? The role of autonomy-supportive teaching and students’ autonomous motivation - Krpanec, Eta; Popović, Dora; Babarović, Toni (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
Agentic engagement is a relatively new construct within the self-determination theory framework which refers to students’ constructive contributions to the flow of the class. Previous research has linked agentic engagement with better student outcomes; therefore, it is important to investigate factors that could encourage it. Studies suggest that autonomy-supportive teaching promotes agentic engagement. However, little investigation has been made into the mechanisms underlying this association. Hence, the aim of this study was to examine the relationship between teachers’ autonomy support and students’ agentic engagement, and to determine whether it is mediated by the students’ autonomous motivation. Additionally, it was investigated if these relationships vary between students who attend different high school programs. The participants were 327 high school students, of which 74% attended a gymnasium program. The analysis concluded that autonomy-supportive teaching is positively associated with agentic engagement, and that the relationship is partially mediated by autonomous motivation. Furthermore, high school program was not found to be a significant moderator of the relationships. The tested model explained about 30% of the agentic engagement variance. The findings suggest the teachers should aim to encourage students’ autonomy if they want them to be actively involved in class.